Levels of Glucagon-like Peptide 1 are Decreased in Macrosomic Neonates from Non-Diabetic Mothers - Aktulay, Ayla; Engin-Ustun, Yaprak; Yasar, Ozlem Gunduz; Yilmaz, Canan; Erkaya, Salim; Ozgu-Erdinc, A. Seval (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Glucagon-like peptide 1 (GLP-1) is a gut-derived peptide with insulin-like effects. Our aim was to analyze cord blood GLP-1 levels of macrosomic and appropriate-gestational-age (AGA) neonates from non-diabetic mothers. A case-control study was conducted with 22 term macrosomic neonates (birth weight≥4000 g) and 22 AGA (birth weight>10th percentile and<4000 g) pregnancies. Cord blood GLP-1 levels of neonates were measured. There were no significant differences in maternal age, gestational age and gravida between the 2 groups. Umbilical cord blood GLP-1 levels were significantly lower in macrosomic neonates (6.9±2.9 pg/mL) compared with control group (10.3±3.7 pg/mL) (p=0.002). Binary logistic regression analysis showed only the maternal BMI to be an independent statistically significant predictor of macrosomia (odds ratio=2.459; 95% CI, 1.170–5.170; P=0.018). The results of our study revealed decreased GLP-1 levels in macrosomic neonates, and maternal BMI was an independent predictor of macrosomia.
Keywords: Glucagon-like peptide 1; macrosomia